Immunomodulatory Effect of Recombinant Chicken Interferon-gamma (rchIFN-γ) on Specific and Non-specific Immune Responses in Chicken Vaccinated Against Newcastle Disease Virus (NDV) - Binjawadagi, Basavaraj; Babu, Y. Hari; Sreekumar, E. (International Journal of Poultry Science, 2009)
Present study was undertaken to evaluate the immunomodulatory effect of recombinant chicken interferon -gamma (rchIFN-γ) on specific and non-specific immune responses in chicken vaccinated against Newcastle Disease Virus (NDV). A total of 180 day old layer chicks (BV-300) were divided into three groups. Test Group I (TG-I) (64 chicks) was injected with 5 microgram/chick subcutaneously of rchIFN-γ along with ND vaccinations (LaSota and R2B strains), Test Group II (TG-II) (64 chicks) was injected with same dose and route of rchIFN-γ 6 h after ND vaccinations on both occasions, whereas, third group remained as vaccinated control group (52 chicks). Haemagglutination Inhibition (HI) test and Migration Inhibition (MI) in percentages estimated by Leukocyte Migration Inhibition Test (LMIT) were conducted to evaluate humoral and cell mediated immune responses respectively. Nitroblue Tetrazolium (NBT) reduction assay was conducted to evaluate the non-specific immune response by estimating the Phagocytic Index (PI) in percentages. The test results revealed that, significantly (p< 0.05) increased specific (humoral and cell mediated) and non-specific immune responses were recorded in the groups treated with rchIFN-γ i.e., higher results when given along with the vaccine and highest results when given 6 h after vaccinations. The results advocated that, rchIFN-γ may be used as an immunopotentiator in chicken vaccinated against NDV.